The Effects of Increased Body Temperature on Motor Control during Golf Putting - Mathers, John F.; Grealy, Madeleine A. (Frontiers in Psychology, 2016)
Abstract This study investigated the effect of increased core temperature on the performance outcome and movement kinematics of elite golfers during a golf putting task. The study aimed to examine individual differences in the extent to which increased temperature influenced the rate of putting success, whether increased temperature speeded up the timing of the putting downswing and whether elite golfers changed their movement kinematics during times of thermal stress. Six participants performed twenty putts to each of four putt distances (1 m, 2 m, 3 m, and 4 m) under normal temperature conditions and when core body temperature was increased. There was no significant difference in the number of successful putts between the two temperature conditions, but there was an increase in putterhead velocity at ball impact on successful putts to distances of 1 m and 4 m when temperature was elevated. This reflected an increase in swing amplitude rather than a reduction in swing duration as hypothesised. There were individual differences in the motor control response to thermal stress as three of the golfers changed the kinematic parameters used to scale their putting movements to achieve putts of different distances at elevated temperatures. Theoretical implications for these findings and the practical implications for elite golfers and future research are discussed.